First 1000 Days and Beyond After Birth: Gut Microbiota and Necrotizing Enterocolitis in Preterm Infants - Zeng, Shuqin; Ying, Junjie; Li, Shiping; Qu, Yi; Mu, Dezhi; Wang, Shaopu (Frontiers in Microbiology, 2022)
Preterm birth remains a major maternal and infant health issue worldwide particularly with an increase in the global preterm birth rate, which requires more interventions to manage the consequences of preterm birth. In addition to traditional complications, recent studies have indicated the succession of gut microbiota of infants born preterm is disordered due to the systemic physiological immaturity, which confers negative influences on the growth, development and health of infants. Here we briefly discuss the prevalence of preterm birth worldwide, and then highlight the signatures of gut microbiota in preterm infants within the first 1000 days of life after birth categorized into birth, infancy, and childhood. Afterwards, the potential association of clinical phenotypes typically associated with preterm birth (i.e. necrotizing enterocolitis) with gut microbiota is focused, and the potential directions for future studies of this field are finally discussed.